Experiments in Processing Castengel with Tempe Flour as a Substitute Wheat Flour - Inggriyanita, Linda Putri; Mulyantari, Enny Mulyantari; Prasetyanto, Hermawan (Gastronary, 2023)
kastengel is a dry cake made from wheat flour. Wheat flour contains a protein called gluten. However, there are some people who cannot consume gluten, so a substitution of wheat flour is needed. Tempe is a food made from soybeans which does not contain gluten, so tempeh can be processed into flour to replace wheat flour. The use of tempe flour as a substitute for wheat flour will certainly be healthier, because it is free of gluten. In addition, tempeh is affordable and can add variety to the processing of tempeh. This study with 30 respondents aimed to find out whether tempe flour could be used as a raw material in processed kastengel cakes and to determine the preference level of tempe flour kastengel based on aspects of taste, aroma, color and texture. The analytical method used is the hedonic test with 4 levels of assessment (Very Like, Like, Dislike, Strongly Dislike) and also uses a sensory test. Data analysis was carried out through questionnaires and interviews with respondents. From the results of the hedonic test and sensory test, the taste aspect gets the Very Like category with an average value of 3.8; the color aspect and the texture aspect get the Very Like category with an average value of 3.7; and the aroma aspect gets the Like category with an average value of 3.47. Based on the results of the study, it can be concluded that tempeh castor flour can be used as the basic ingredient for making kastengel and is preferred by respondents based on aspects of taste, aroma, color and texture.